A COMPARATIVE ANALYSIS OF EASTERN AND WESTERN PHILOSOPHICAL PHILOSOPHY BY AHMED ZACKI VALIDIAN FLOOD IN HIS "METHOD IN HISTORY - Xujaev, Muminjon Isoxonovich (International Journal of Psychosocial Rehabilitation, 2020)
This paper investigates a comparative analysis of eastern and western philosophical philosophy by Ahmed Zacki validian flood in his "method in history". On this case, methodological and theoretical background have been investigated to get better development. Finally, outcomes and shortcomings were noticed to make further analyses.